Two Rare Complications in One Patient: Acquired von Willebrand Syndrome Associated with Intracranial Plasmacytoma. (27th August 2019) - Auge, H.; Yguel, C.; Schmitt, E.; Frotscher, B.; Busby-Venner, H.; Morizot, R.; Moulin, C.; Feugier, P.; Perrot, A.; Filliatre-Clement, L.
Abstract : Here, we describe a rare case of acquired von Willebrand syndrome (VWS) associated with intracranial plasmacytoma. The literature includes reports of a few cases of plasmacytoma with central nervous involvement, but none of them with acquired VWS. Diagnosis was made based on a stereotaxic intracerebral biopsy. During this biopsy, a ventriculoperitoneal shunt was established, which was complicated with abnormal bleeding. Subsequent hemostasis assessment related to hemopathy revealed acquired von Willebrand disease. The patient received induction therapy with bortezomib, thalidomide, and dexamethasone (VTD), followed by high-dose melphalan chemotherapy and autologous stem cell transplantation, and then VTD consolidation, and finally maintenance with lenalidomide. Our patient currently remains in very good partial response without neurological symptoms after 4 months of maintenance. The patient is free of progression 14 months after their original presentation.